Mortality pattern in Emergency Department of a Tertiary Care Center in Western Nepal - Shakya, Raju Prasad; Adhikari, Suraj; Munankami, Salina (Journal of Nobel Medical College, 2018)
Background : There is abundance of evidence regarding various aspects of mortality in emergency department from different parts of world but there is limited number of studies on mortality in context of western Nepal. The objectives of this analysis were to review the demographical pattern of mortalities and define the cause and frequency of death in the Emergency Department (ED) of our institute within 24 hours of treatment process.Material and Methods : A retrospective study was carried out evaluating all patients who died during the treatment process in the Emergency Department of Lumbini Medical College in a three and half year of period from January 2014 to June 2017.Results : A total of 33,472 patients attended to ED with mortality rate of 36.4%, 33.6% and 28.2% on consecutive three years in which 110 deaths occurred. There were 66 (60%) male and 44 (40%) female. The highest mortality was seen after age of 60 years (range 2 month to 90 year). Non-communicable causes & stroke deaths were found to be higher in number. Most of our patient n=52 (47.3%) death occurred within 6-12 hours of admission in ED.Conclusion : Mortality within 24 hours of presentation at ED remains high. Well organized emergency setup, transport, development of protocol as well as new guideline will definitely help in reducing hospital mortalities.Journal of Nobel Medical CollegeVolume 6, Number 2, Issue 11 (July-December, 2017) Page:48-52